Use of benthic macroinvertebrates as bioindicators of water quality in Rímac River, Lima-Callao, Perú - PAREDES-E., CHRISTIAN; IANNACONE-O., JOSÉ; ALVARIÑO-F., LORENA (Revista Colombiana de Entomología, 2005)
The communities of benthic macroinvertebrates (BMI) can be used as efficient biological indicators of the water quality in fresh aquatic ecosystems. Between October 2002 and September 2003, evaluations of MIB were developed in the Rímac River downstream from Atarjea, LimaCallao, Peru. The objective was to analyze their faunistic composition, richness of families and water quality, based on the modified Biological Monitoring Working Party index (BMWP´ modified). The evaluation was conducted in six sampling stations located along the course of the Rimac river that crosses Lima and Callao. Thirty-five taxa of BMI were reported: Hexapoda (27), Annelida (2), Mollusca (2), Arachnidae (2), Plathyhelmintes (1) and Chilopoda (1). From 2,166 specimens collected, Oligochaeta (n = 597) had the higher absolute abundance, followed by Psychodidae (n = 521), Physidae (n = 442), Chironomidae (n = 300), and Dixidae (n = 168). The modified BMWP´ index scored the water of Rimac River downstream from Atarjea as critical quality or very polluted waters (29 points). Of all the physicochemical analyses evaluated, Biochemical Oxygen Demand indicated perturbance effects in this freshwater ecosystem. Finally, the potential of the BMI to evaluate the water quality of the rivers in Peru is analyzed.